2022
DOI: 10.1111/nph.18173
|View full text |Cite
|
Sign up to set email alerts
|

SubPhaser: a robust allopolyploid subgenome phasing method based on subgenome‐specific k‐mers

Abstract: Summary With advanced sequencing technology, dozens of complex polyploid plant genomes have been characterized. However, for many polyploid species, their diploid ancestors are unknown or extinct, making it impossible to unravel the subgenomes and genome evolution directly. We developed a novel subgenome‐phasing algorithm, SubPhaser, specifically designed for a neoallopolyploid or a homoploid hybrid. SubPhaser first searches for the subgenome‐specific sequence (k‐mer), then assigns homoeologous chromosomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 43 publications
1
58
0
Order By: Relevance
“…unravelled the complex ancestry and domestication history of cultivated strawberry and found that nucleotide diversity and heterozygosity were significantly lower in cultivated strawberries [ 15 ]. But the hypothesis on hybrid ancestry of octoploid cultivated strawberry was controversial [ 16 , 17 ]. Cauret et al .…”
Section: Introductionmentioning
confidence: 99%
“…unravelled the complex ancestry and domestication history of cultivated strawberry and found that nucleotide diversity and heterozygosity were significantly lower in cultivated strawberries [ 15 ]. But the hypothesis on hybrid ancestry of octoploid cultivated strawberry was controversial [ 16 , 17 ]. Cauret et al .…”
Section: Introductionmentioning
confidence: 99%
“…2–4 and Supplementary Figs 27 – 34 ). Leveraging the recent developments in subgenome-phasing method published by Jia et al 4 , we propose an alternative model, i.e., reticulate allopolyploidization, to account for the evolution and the genomic diversity of these three Papaver species. Our hypothesis is supported by the following lines of evidence: We extracted 4,791 anchor genes from the inter-genomic syntenic blocks at a ratio of 1:2:4 in P. rhoeas , P. somniferum and P. setigerum using OrthoFinder v2.3.1 5 and MCScanX 6 (Supplementary Figs.…”
mentioning
confidence: 99%
“…The 95% confidence intervals (CI) of the insertion times are used to infer the time boundary of divergence to hybridization period. We phased the subgenomes of P. somniferum and P. setigerum using SubPhaser v1.2 4 (Supplementary Fig. 1B, C , Supplementary Figs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We assembled genomes of three Papaver species, P. somniferum, P. rhoeas and P. setigerum , and revealed two-round whole genome duplication (WGD) events and the punctuated patchwork evolution of morphinan and noscapine biosynthesis pathway based on comparative genomic analyses of collinearity, phylogenetic tree, and synonymous substitution rate ( Ks ) at species level 1 . Recently, Zhang et al reanalyzed our three Papaver genomes based on the subgenome-phasing analysis by their newly published tool SubPhaser 2 . They confirmed the two WGDs we previously detected, but provide strong evidence that the WGDs were likely allopolyploidy events.…”
mentioning
confidence: 99%